A relevância do pensar reflexivo e sua tradução na ação humana - de Paulo, Camila Silva; de Oliveira, José Luíz (Revista Vozes dos Vales: Publicações Acadêmicas, 2020)
The faculty of thinking is a theme deeply addressed by Arendt in his work The Life of the Spirit, however, it is by analyzing the judgment of Eichmann, the partisan of the Nazi totalitarian regime responsible for leading thousands of Jews to death, that it will corroborate the implications of the process of reflective thinking or its absence. In an analysis of the facts that could have led not only Eichmann, but anyone to commit atrocious and unimaginable acts, the German philosopher ponders the origins and necessary bases for the establishment of a totalitarian system in society. Discussing in detail from the process of massification of man, until the moment of obtaining soldiers with ’blind and cadaverous’ obedience, the thinker elaborates concepts and analyses of paramount importance. The concept of banality of evil associated with the inability to think, developed by the author in the face of the analysis of Eichmann’s judgment, will configure the idea that the faculty of judgment is directly linked to the faculty of thinking, if what is objective is a judgment measured, wise and consequently wise, and not a judgment based on alienation. The faculty of thinking in its reflective character is such that it can lead man to better judge, and thus refrain from committing evil.